2020
DOI: 10.3390/agronomy11010046
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Phomopsis juglandina (Sacc.) Hohn. Associated with Dieback of Walnut in the Climatic Conditions of Southern Romania

Abstract: Phomopsis juglandina (Sacc.) Höhn., which is the conidial state of Diaporthe juglandina (Fuckel) Nitschke, and the main pathogen causing the dieback of branches and twigs of walnut was recently detected in many orchards from Romania. The symptomatological, morphological, ultrastructural, and cultural characteristics, as well as the pathogenicity of an isolate of this lignicolous fungus, were described and illustrated. The optimum periods for infection, under the conditions prevailing in Southern Romania, mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Walnut woody parts are commonly invaded by trunk pathogens, including Diatrypaceae, Diaporthaceae, Botryosphaeriaceae and Togniniaceae. In general, the spread of these fungi is similar in regions and countries such as: California (Diaporthe, Neofusicoccum) Agustí-Brisach et al, 2019), Chile (Diaporthe, Diplodia, Neofusicoccum) (Díaz et al, 2018;Luna et al, 2022), China (Botryoshpaeria, Lasiodiplodia, Neofusicoccum) (Yu et al, 2015;Li et al, 2016), the Czech Republic (Cadophora, Cryptovalsa, Diaporthe, Diplodia, Dothiorella, Eutypa, Eutypella, Peroneutypa, Phaeoacremonium) (Eichmeier et al, 2020), Italy (Botryosphaeria, Neofusicoccum) (Gusella et al, 2021), Romania (Diaporthe) (Mihaescu et al, 2020), Spain (Botryosphaeria, Diaporthe, Diplodia, Dothiorella, Neofusicoccum) (López- Moral et al, 2020a;Moral et al, 2010), and Turkey (Botryosphaeria, Neofusicoccum) (Kara et al, 2021;Yildiz et al, 2022). Walnut wood also hosts Ca.…”
Section: Fungal Trunk Diseases Of Nut Treesmentioning
confidence: 99%
“…Walnut woody parts are commonly invaded by trunk pathogens, including Diatrypaceae, Diaporthaceae, Botryosphaeriaceae and Togniniaceae. In general, the spread of these fungi is similar in regions and countries such as: California (Diaporthe, Neofusicoccum) Agustí-Brisach et al, 2019), Chile (Diaporthe, Diplodia, Neofusicoccum) (Díaz et al, 2018;Luna et al, 2022), China (Botryoshpaeria, Lasiodiplodia, Neofusicoccum) (Yu et al, 2015;Li et al, 2016), the Czech Republic (Cadophora, Cryptovalsa, Diaporthe, Diplodia, Dothiorella, Eutypa, Eutypella, Peroneutypa, Phaeoacremonium) (Eichmeier et al, 2020), Italy (Botryosphaeria, Neofusicoccum) (Gusella et al, 2021), Romania (Diaporthe) (Mihaescu et al, 2020), Spain (Botryosphaeria, Diaporthe, Diplodia, Dothiorella, Neofusicoccum) (López- Moral et al, 2020a;Moral et al, 2010), and Turkey (Botryosphaeria, Neofusicoccum) (Kara et al, 2021;Yildiz et al, 2022). Walnut wood also hosts Ca.…”
Section: Fungal Trunk Diseases Of Nut Treesmentioning
confidence: 99%
“…Some species of Diaporthe (= Phomopsis ) produce different types of conidia, which are known as alpha, beta or gamma [ 36 ]. Mihaescu et al [ 37 ] reported alpha and beta conidia from the pycnidia formed in cultures of Phomopsis juglandina (Sacc.) Hohn.…”
Section: Cultures In Traditional Taxonomy (Ie Morphology-based Taxonomy)mentioning
confidence: 99%